2003
DOI: 10.1029/2003gl017390
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave splitting in a young continent‐continent collision: An example from Eastern Turkey

Abstract: We have determined the shear wave splitting fast polarization direction and delay time using data from the ETSE broadband experiment (Eastern Turkey Seismic Experiment), a deployment of 29 broadband seismic stations across the collision zone of the Arabian, Eurasian, and Anatolian plates. Our results show that the fast polarization directions are relatively uniform and they exhibit primarily NE–SW orientations. No abrupt changes in anisotropy directions are observed across the main tectonic units in the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 19 publications
11
92
1
5
Order By: Relevance
“…The results of the project suggested that mantle lithosphere is either absent or extremely thin beneath the eastern Anatolian Plateau (AlLazki et al, 2003;Gök et al, 2003;Sandvol et al, 2003). The thickness of the lithospheric mantle in the Eastern Anatolian region is ~60 km (e.g., Pearce et al, 1990;Al-Lazki et al, 2003;Gök et al, 2003;Sandvol et al, 2003). This is much less than the 100-125 km thickness of the cold and stable mantle lithosphere in the Arabian Shield and Iranian Plateau (e.g., Angus et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the project suggested that mantle lithosphere is either absent or extremely thin beneath the eastern Anatolian Plateau (AlLazki et al, 2003;Gök et al, 2003;Sandvol et al, 2003). The thickness of the lithospheric mantle in the Eastern Anatolian region is ~60 km (e.g., Pearce et al, 1990;Al-Lazki et al, 2003;Gök et al, 2003;Sandvol et al, 2003). This is much less than the 100-125 km thickness of the cold and stable mantle lithosphere in the Arabian Shield and Iranian Plateau (e.g., Angus et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The recorded delay time between these two components is a function of the severity of the anisotopy and the thickness of the anisotropic layer. The shear wave anisotropy studies that I use here are representative down to a depth of around 200 km or more in eastern Turkey (34) and the eastern part of NAFZ (35) being possibly shallower farther west (36). P n waves, on the other hand, propagate typically below the Moho discontinuity along approximately horizontal rays apart from source and receiver legs.…”
mentioning
confidence: 99%
“…Therefore, it is more meaningful to compare the P n anisotropy directions with geodetically measured strain rates rather than velocities [see (40) for a study in which P n anisotropy is used to measure the width of mantle deformation across a Continental Transform]. In my analysis, I use the SKS fast-splitting directions from (34)(35)(36)41) for the Aegean, central and eastern parts of the NAF, eastern Turkey, and Dead Sea Transform, respectively (see Fig. 2).…”
mentioning
confidence: 99%
“…In the evaluation of the region, the marine and continental basins have significant roles. The seismological studies (Al-Lazki et al, 2003;Türkelli et al, 2003;Sandvol et al, 2003aSandvol et al, , 2003bZor et al, 2003) realized for characterizing the compressional zone of the region and defining the geodynamics of the compression since 2003, the evolution was explained in the light of the studies and the presence of asthenospheric upwelling was determined (fiengör et al, 2003;Keskin 2003Keskin , 2007. It is expected that this upwelling causes to reduce the density of the subsurface formation with the effect of the high temperature and accordingly, brings along the reduction on values of the gravity anomalies.…”
Section: Resultsmentioning
confidence: 99%